2021
DOI: 10.1186/s12866-021-02303-1
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating bacterial adhesion to mucosal surface by an original AFM approach

Abstract: Background Fish skin represents an ancient vertebrate mucosal surface, sharing characteristics with other mucosal surfaces including those of the intestine. The skin mucosa is continuously exposed to microbes in the surrounding water and is therefore important in the first line defense against environmental pathogens by preventing bacteria from accessing the underlying surfaces. Understanding the microbe-host interactions at the fish skin mucosa is highly relevant in order to understand and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Another study by Herman-Bausier et al examined the adhesion of Staphylococcus aureus collagen binding protein Cna which demonstrated binding forces of ~ 1.2 nN to collagen, which was disrupted by multiple mAbs, including 9G7, C2 and 11H11 41 . Some studies have explored using AFM to measure bacterial glycan interactions with mAbs, lectins 42 44 , and, with regard to H. pylori , Parreira et al demonstrated the mechanistic binding method between H. pylori blood-group binding adhesin (BabA) and Lewis B 29 . Parreira et al also highlighted the potential for AFM in the development of new targeted therapies against bacteria 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Herman-Bausier et al examined the adhesion of Staphylococcus aureus collagen binding protein Cna which demonstrated binding forces of ~ 1.2 nN to collagen, which was disrupted by multiple mAbs, including 9G7, C2 and 11H11 41 . Some studies have explored using AFM to measure bacterial glycan interactions with mAbs, lectins 42 44 , and, with regard to H. pylori , Parreira et al demonstrated the mechanistic binding method between H. pylori blood-group binding adhesin (BabA) and Lewis B 29 . Parreira et al also highlighted the potential for AFM in the development of new targeted therapies against bacteria 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The adhesive force of S. putrefaciens WS13 was measured by AFM (Bioscope resolve, Bruker, Germany) as described ( 29 ).…”
Section: Methodsmentioning
confidence: 99%